Environmental and ecological factors associated with stinging jellyfish at a tourism hotspot in the Gulf of Thailand - Rahul Mehrotra; Pasicha Chaikaew; Elouise Haskin; Kirsty Magson; Chad M. Scott; Ruth Doherty (Estuarine, Coastal and Shelf Science, 2024)

Integrating Shared Socioeconomic Pathway-informed adaptation into temperature-related mortality projections under climate change - Kai Wan; Shakoor Hajat; Ruth M. Doherty; Zhiqiang Feng (Environmental Research, 2024)

Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Lucy C. M. Omeyer; Philip D. Doherty; Sarah Dolman; Robert Enever; Allan Reese; Nicholas Tregenza; Ruth Williams; Brendan J. Godley (Frontiers in Marine Science, 2020)

Implications of future climate and atmospheric CO 2 content for regional biogeochemistry, biogeography and ecosystem services across East Africa - RUTH M. DOHERTY; STEPHEN SITCH; BENJAMIN SMITH; SIMON L. LEWIS; PHILIP K. THORNTON (Global Change Biology, 2010)
We model future changes in land biogeochemistry and biogeography across East Africa. East Africa is one of few tropical regions where general circulation model (GCM) future climate projections exhibit a robust response of strong future warming and general annual‐mean rainfall increases. Eighteen future climate projections from nine GCMs participating in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment were used as input to the LPJ dynamic global vegetation model (DGVM), which predicted vegetation patterns and carbon storage in agreement with satellite observations and forest inventory data under the present‐day climate. All simulations showed future increases in tropical woody vegetation over the region at the expense of grasslands. Regional increases in net primary productivity (NPP) (18–36%) and total carbon storage (3–13%) by 2080–2099 compared with the present‐day were common to all simulations. Despite decreases in soil carbon after 2050, seven out of nine simulations continued to show an annual net land carbon sink in the final decades of the 21st century because vegetation biomass continued to increase. The seasonal cycles of rainfall and soil moisture show future increases in wet season rainfall across the GCMs with generally little change in dry season rainfall. Based on the simulated present‐day climate and its future trends, the GCMs can be grouped into four broad categories. Overall, our model results suggest that East Africa, a populous and economically poor region, is likely to experience some ecosystem service benefits through increased precipitation, river runoff and fresh water availability. Resulting enhancements in NPP may lead to improved crop yields in some areas. Our results stand in partial contradiction to other studies that suggest possible negative consequences for agriculture, biodiversity and other ecosystem services caused by temperature increases.

Spatial Scale Effects of Climate Scenarios on Simulated Cotton Production in the Southeastern U.S.A. - Ruth M. Doherty; Linda O. Mearns; K. Raja Reddy; Mary W. Downton; Larry McDaniel (Climatic Change, 2003)

A gridded reconstruction of land and ocean precipitation for the extended tropics from 1974 to 1994 - Ruth M. Doherty; Mike Hulme; Colin G. Jones (International Journal of Climatology, 1999)